ANALISIS PENERAPAN METODE PENYUSUTAN ASET TETAP TERHADAP PENINGKATAN LABA PERUSAHAAN PADA PT. PUTRA MEKAR JAYA - Ali Muhajir (Fakultas Ekonomi, 2023)
This study aims to determine the application of depreciation methods at PT. Putra Mekar Jaya is in accordance with the assumptions of Financial Accounting Standards and the impact of various methods of depreciating fixed assets on company profits. The research method is qualitative and historical research. The results of this study are the application of a straight line method to the office and building inventory. Butfor vehicles it is not appropriate and should be changed by the declining balance method. Then the depreciation method used has an impact on company profits. So that we can know the profit reported at PT. Putra Mekar Jaya by using the straight-line method higher than the declining balance method and the methodfor the number ofyears.